1991
DOI: 10.1111/j.1526-4610.1991.hed3109582.x
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Visual Aura: A Totally New Variation of Migraine

et al.

Abstract: An unusual case of an abnormally long-lasting (over 12 months) visual migraine aura is reported. The absence of signs of a structural lesion, as shown by neuro-imaging and clinical investigations, make difficult the differential diagnosis between a new variation and a complication of migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 1 publication
(1 reference statement)
1
28
0
Order By: Relevance
“…Only 10 out of 20 cases of sustained visual aura reported in the literature have been studied with Tc99m‐HMPAO SPECT. The study of rCBF in patients with persistent aura limited to one hemifield showed more frequently, as has been demonstrated in typical migrainous aura, a hypoperfusion in the posterior regions of the contralateral cerebral cortex (three patients) (5, 9), and, more rarely, a hypoperfusion of the whole hemisphere (one patient) (4). Of the six patients who complained of sustained aura that involved all the visual field, three had an oligoemia in the posterior regions of the cerebral cortex bilaterally and one in the left temporal lobe, whereas two showed a normal SPECT (5).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Only 10 out of 20 cases of sustained visual aura reported in the literature have been studied with Tc99m‐HMPAO SPECT. The study of rCBF in patients with persistent aura limited to one hemifield showed more frequently, as has been demonstrated in typical migrainous aura, a hypoperfusion in the posterior regions of the contralateral cerebral cortex (three patients) (5, 9), and, more rarely, a hypoperfusion of the whole hemisphere (one patient) (4). Of the six patients who complained of sustained aura that involved all the visual field, three had an oligoemia in the posterior regions of the cerebral cortex bilaterally and one in the left temporal lobe, whereas two showed a normal SPECT (5).…”
Section: Discussionmentioning
confidence: 61%
“…It has also been hypothesized that sustained reverberating waves of SD may be implicated. The results of SPECT and PET studies evaluating, respectively, CBF and cerebral metabolism have supported this hypothesis (4, 5, 8, 9).…”
Section: Discussionmentioning
confidence: 83%
“…Central vision loss or blurring may also occur as part of the aura. 13,27 Additional symptoms include paroxysmal vertigo, hemisensory dysesthesias, and rarely auditory hallucinations. Acephalic migraine should be differentiated from transient ischemic attack, occipital or temporal lobe seizures, or optic nerve disease.…”
Section: Typical Aura Without Headachementioning
confidence: 99%
“…The first reported case of PMA was in a patient with a history of migraine who had a typical migraine with aura attack and then had persistent visual aura for greater than 12 months. 6 A further sub-classification has been proposed which separates PMA into two forms, PMA with typical aura (PMA-TA) and PMA with persistent visual disturbance (PMA-PPVD). In PMA-TA, patients experience persistent symptoms of their typical migraine aura.…”
Section: Persistent Aura Without Infarction (Pma)mentioning
confidence: 99%
“…When aura symptoms persist for ≥1 week with no evidence of infarction on neuroimaging, the symptoms fulfill criteria for 1.4.2 Persistent aura without infarction (PMA). The first reported case of PMA was in a patient with a history of migraine who had a typical migraine with aura attack and then had persistent visual aura for greater than 12 months . A further sub‐classification has been proposed which separates PMA into two forms, PMA with typical aura (PMA‐TA) and PMA with persistent visual disturbance (PMA‐PPVD).…”
Section: Introductionmentioning
confidence: 99%